Using Noddy Cartoon to Improve the Writing Skill of the First Year Students of SMK Terpadu Mega Rezky Makassar - Tanasy, Novalia (Universitas Cokroaminoto Palopo, 2017)
This research is conducted to find out: (1) whether or not the use of Noddy cartoon is effective in improving the writing skill of the first year students of SMK Terpadu Mega Rezky Makassar and (2) the attitude of the first year students of SMK Terpadu Mega Rezky Makassar toward the use of Noddy cartoon in improving their writing skill. The research employs quasi-experimental method with two groups namely control and experimental groups. Each group consists of 30 students. The sample is chosen by applying cluster random sampling technique. The writer uses a test of writing and questionnaire in experimental group. The data obtained through the test is analyzed by using inferential statistic through SPSS version 22.0 program. The Likert-scale is used to analyze data of the studentâs response to the questionnaire. In conducting the research, the writer applies Noddy cartoon episodes as the medium in improving the studentsâ writing skill. The result of this research shows that the use of Noddy cartoon is effective in improving the writing skill achievements of the first year students of SMK Terpadu Mega Rezky Makassar. It is indicated by the significant difference between the result of post-test in the experimental and control groups. The mean score of post-test in the experimental group is 76.77, which is higher than the mean score of post-test in the control group which is only 65.97. Furthermore, the data that are collected from the questionnaire show that the students have positive attitude towards the use of Noddy cartoon in learning writing, which is in scale of 83.20 or categorized as positive.